INTERNATIONAL COOPERATION POTENTIAL: ESSENCE, CHALLENGES, AND RECOVERY PATHWAYS FOR UKRAINE'S TOURISM AND HOSPITALITY - SEMYKINA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article addresses the essence, challenges, and development directions of international cooperation potential in Ukraine's tourism and hospitality sector as a strategic lever for overcoming war consequences and ensuring sector modernization. The study clarifies international cooperation as complex, purposeful interaction of state, private, and public actors across multiple levels aimed at joint problem-solving and achieving synergistic effects for sustainable development. The research systematizes a comprehensive set of interrelated challenges and threats facing Ukraine's tourism and hospitality sector: security risks from military operations and mine hazards, infrastructure destruction affecting hotels and cultural heritage sites, human capital crisis due to migration and mobilization, economic downturn with reduced demand and investment freezing, negative international image, and institutional barriers to investment attraction and risk insurance. The article substantiates six priority directions for developing international cooperation potential: institutional cooperation through bilateral agreements and coordination mechanisms; financial and investment support via development funds and public-private partnerships; human capital development through joint educational programs and international internships; innovation and digitalization using digital platforms and virtual tours; marketing and promotion through joint international campaigns; and security and standardization via harmonization with international standards. The study emphasizes the necessity of a differentiated approach to implementing these directions during wartime versus the post-war period. During the war, priorities include preserving human capital through online training, planning future projects, and managing Ukraine's international image. Following war's conclusion, focus shifts to large-scale infrastructure reconstruction, intensive international marketing campaigns, and reopening tourism routes in de-occupied territories. The research underscores the critical importance of comprehensive investigation into financial-economic mechanisms for activating international partnership to ensure effective sector recovery and modernization.
Keywords: international cooperation; tourism and hospitality; development potential; challenges and threats; recovery directions; wartime conditions; post-war reconstruction; partnership mechanisms